Reading the poems in Abbasid era The time and place In poem (Comes to the Creation of darkness and sunshine) to Abi Alaa AL-Maarri - Al-Mualid, Rawda (Journal of Humanities & Social Sciences, 2018)
This study dealt with a poem about (Comes to the Creation of darkness and sunshine) to Abi Alaa al-Maarri، according to a study of the temporal dimension (The time and place) of the poem. In spite of the existence of studies that touched upon the poetry of Al-Ma'ri from the technical and historical point of view، to read this poem and analyze it، and to discover the types of entry in it. The study aimed to read the poem a different reading.Through the focus on the poetic space، which allows the reader to dig deep in the poetic text، and explore the meanings of the meanings، discover the poetic state of the poet، and reflect the aesthetic values in the text characteristic of the poet's view of life، through the linguistic connotations that the study is trying to be questioned. The study concluded the results of the most important: the diversity of places at Abu Alaa Maari، there is the finite place in the grave and the open and closed place، and the enemy and the kind، all indicate psychological connotations full of the heart of the poet. The time also highlighted the experiences and emotions that accompanied the poetic state of the poet، as time has elucidated the psychological significance associated with the feeling of the poet.
Keywords: temporal; Abu al-Ala' al-Ma'ari; the finite in greatness; the open; the closed; the hostile; the pet; the absolute; the restricted